An Allene Approach to Tetrahydrofuran‐Fused Bicyclo[2.2.2]oct‐2‐enes. Issue 5 (27th December 2017) - Song, Shihua; Fu, Chunling; Huang, Xin; Ma, Shengming
Abstract: An efficient access to tetrahydrofuran‐fused bicyclo[2.2.2]oct‐2‐enes via palladium‐catalyzed cyclization of oxygen‐tethered 2, 7‐alkadiynylic carbonates with 2‐(buta‐2, 3‐dienyl)malononitrile has been developed. Perfect chiral induction was observed when a substituent was introduced to the propargylic position affording the optically active polycyclic products of both enantiomers. Control experiments showed that the oxygen tether of 2, 7‐alkadiynylic carbonates and the two cyano groups in allene are indispensible for this transformation. Abstract :